[József Dvihally 8]
1930 wedding, family competition in the garden, visiting old ladies in the Margaret-island, 1929 holiday in Naszvad, guests arriving, boy's hand bandaging, chicken, gardening, in the cemetary, 1930 Érsekújvár, celebrating the reannexation, procession, 100 years old high-school in Érsekújvár, 1936 the map of "Greater Hungary", Tihany, Annimal and Agricultural Fair, the statue of Ferenc Rákóczi and Lajos Kossuth, motorcycle race, Intarnational Fair, procession around the Basilika, scout's meeting, fashion show, Miklós Horthy bridge (today Szabadság-bridge), the Holy Land museum in Hűvösvölgy, military celebration in Esztergom, school-closing sport competition in th Benedictine high school, prelates praying, rests of the previous rolls,